Adams y Victor : Principios de neurología - Ropper, Allan H. (McGraw-Hill Interamericana Editores, S. A. de C. V.s, 2017)
Provides the treatment and management strategies needed to confidently handle both common and rare neurologic conditions. This volume describes the various categories of neurologic disease and the main diseases that constitute each.